2011
DOI: 10.1590/s0104-11692011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and risk factors for type 2 diabetes: a study with health workers

Abstract: We aimed to analyze the interrelationships between occupation and prevalence of risk factors for type 2 diabetes in workers at a hospital in Fortaleza-CE. Cross-sectional study with 299 subjects and form-based, covering socio-demographic concerns and risk factors for Type 2 Diabetes. Results showed that 40.5% of the sample were nursing workers, 63.9% were women, 68.6% were under 35 years of age, 49.5% had an education level equivalent to high school and 51.9% had no marriage or stable union. Comparison among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
0
14
0
4
Order By: Relevance
“…(9) In adults prevalence was even higher: 47.1% were overweight, 30.7% had abdominal obesity and 70,9% had a sedentary lifestyle. (10) In this study carried out with adults approximately 98.8% of the sample had some level of risk for type 2 diabetes mellitus whether low, moderate or high. Regarding associated factors, the most prevalent were increased waist circumference (84.0%), followed by physical inactivity (83.3%) and excess weight (57.9%).…”
Section: Discussionmentioning
confidence: 95%
“…(9) In adults prevalence was even higher: 47.1% were overweight, 30.7% had abdominal obesity and 70,9% had a sedentary lifestyle. (10) In this study carried out with adults approximately 98.8% of the sample had some level of risk for type 2 diabetes mellitus whether low, moderate or high. Regarding associated factors, the most prevalent were increased waist circumference (84.0%), followed by physical inactivity (83.3%) and excess weight (57.9%).…”
Section: Discussionmentioning
confidence: 95%
“…Bel/boy oranı ile ilgili son yıllarda yapı-lan çalışmalar, bel/boy oranının BKİ, bel çevresi ve bel/kalça oranına göre kardiyometabolik risk ile tip 2 diyabet riskinin belirlenmesinde daha iyi bir ölçüm olduğu üzerinde durmaktadır (Ashwell, Gunn, & Gibson, 2012;Savva, Lamnisos, & Kafatos, 2013;Ashwell & Gibson, 2014;Bohr, Laurson, & McQueen, 2016). Tip 2 diyabet risk faktörleri ve risk grupları ile ilgili yapılan bir ça-lışmada abdominal obezite ve sedanter yaşam tarzı risk faktörleriyle ilgili olarak hemşirelerde tip 2 diyabet riskinin diğer sağlık profesyonellerine kı-yasla daha yüksek olduğu belirlenmiştir (Almeida, Zanetti, Almeida, & Damasceno, 2011). Bu araş-tırma, hemşirelik bölümü öğrencilerinde tip 2 diyabet riski ve bel/boy oranı ile tip 2 diyabet riski ilişkisinin değerlendirilmesi amacıyla yürütül-müştür.…”
Section: Introductionunclassified
“…33 Previous investigations also validated this fact and showed that rural people had less awareness of blood glucose level and also diabetes in comparison to urban people. 35,36 As in our study a majority of the population had either misconception or poor conception about diabetes and related causes, symptoms, management and also about control of blood glucose level that justifies that rural people are still in the light of education about diabetes and diabetes related management.…”
Section: Discussionmentioning
confidence: 73%
“…32 Another study showed that education had a significant role in diabetic awareness to keep correct blood glucose level. 33 It is known that inactivity or a low quantity of physical activity can be a work associated risk factor for diabetes as considering that some professions or occupations, due to its own nature, reduce professionals' physical activity. 34 In our study it is found that about 34.40% respondents were housewives which clear the fact that women are more prone to diabetes than men due to sedentary working condition.…”
Section: Discussionmentioning
confidence: 99%